Relationships between bone mass and dietary/lifestyle habits in Japanese women at 3–4 months postpartum. (November 2017) - Hoshino, A.; Yamada, A.; Tanabe, R.; Noda, S.; Nakaoka, K.; Oku, Y.; Katayama, C.; Haraikawa, M.; Nakano, H.; Harada, M.; Uenishi, K.; Goseki-Sone, M.
Abstract: Objectives: The relationships between calcaneal bone mass and dietary/lifestyle habits in women at 3–4 months postpartum were examined in the context of osteoporosis prevention. Study design: Cross-sectional survey. Methods: We measured bone mass using calcaneal ultrasound in mothers who brought their 3- to 4-month-old babies to healthcare centers in Japan for health examination and administered a self-report questionnaire on physical characteristics and dietary/lifestyle habits to those who agreed to participate in the survey. Valid data were available for 1220 women (valid response rate, 97.5%). Results: Based on their stiffness score, a measure of bone mass, 70.9% ( n  = 865) of the participants were classified as 'no apparent abnormality (stiffness score ≥78.8)' (low-risk group), 18.2% ( n  = 222) as 'guidance required (≥70.1–<78.8)' (intermediate-risk group), and 10.9% ( n  = 133) as 'complete examination required (<70.1)' (high-risk group), according to the criteria for osteoporosis screening test results. The percentage of individuals with a history of fracture was higher in the guidance required/complete examination required than in the no apparent abnormality group ( P  = 0.016). The analysis of relationships between the consumption frequency of certain foods, such as calcium-rich foodstuffs, and bone mass found that women who reported lower frequencies of milk and dark-colored (beta-carotene rich) vegetables for breakfast consumption had a significantly lower bone mass than those who consumed these foods more often. Furthermore, the guidance required/complete examination required group had a significantly lower calcium intake than the no apparent abnormality group ( P  = 0.022). Conclusions: These results indicate the need to provide postpartum women with dietary education programs to promote healthy eating habits, such as increased consumption of calcium-rich foods, and prevent osteoporosis. Highlights: We revealed the relationships between bone mass and dietary/lifestyle habits in Japanese women at 3–4 months postpartum. Based on their bone mass, 70.9% of the participants were classified as 'no apparent abnormality, ' 18.2% as 'guidance required, ' and 10.9% as 'complete examination required, ' according to the criteria for osteoporosis screening test results. Women who reported lower frequencies of milk and dark-colored vegetables for breakfast consumption had a significantly lower bone mass than those who consumed these foods more often. The guidance required/complete examination required group had a significantly lower calcium intake than the no apparent abnormality group. These results indicate the need to provide postpartum women with dietary education programs to promote healthy eating habits, and prevent osteoporosis.